A neurocognitive investigation of test methods and gender effects in listening assessment. Issue 4 (4th May 2022) - Aryadoust, Vahid; Ng, Li Ying; Foo, Stacy; Esposito, Gianluca
Abstract: This is the first study to investigate the effects of test methods (while-listening performance and post-listening performance) and gender on measured listening ability and brain activation under test conditions. Functional near-infrared spectroscopy (fNIRS) was used to examine three brain regions associated with listening comprehension: the inferior frontal gyrus and posterior middle temporal gyrus, which subserve bottom-up processing in comprehension, and the dorsomedial prefrontal cortex, which mediates top-down processing. A Rasch model reliability analysis showed that listeners were homogeneous in their listening ability. Additionally, there were no significant differences in test scores across test methods and genders. The fNIRS data, however, revealed significantly different activation of the investigated brain regions across test methods, genders, and listening abilities. Together, these findings indicated that the listening test was not sensitive to differences in the neurocognitive processes underlying listening comprehension under test conditions. The implications of these findings for assessing listening and suggestions for future research are discussed.